Law and morals : Warnock, Gillick and beyond - Lee, Simon (Simon F.) (Oxford : Oxford University Press, 1986)
This book examines the relationship between law and morals, especially relating them to issues and events of current interest, and argues for broader participation in the debate, since it raises questions which touch the lives of us all.
Includes bibliographical refrences and index.
Keywords: Law and ethics